Controlled reversible visceral arterial ischemia, venous congestion and combined malperfusion via midline laparotomy in rats - Studier-Fischer, Alexander; Özdemir, Berkin; Kowalewski, Karl-Friedrich; Haney, Caelán Max; Egen, Luisa; Michel, Maurice Stephan; Mieth, Markus; Czigány, Zoltán; Salg, Gabriel Alexander; Nienhüser, Henrik; Billmann, Franck (JoVE journal. Neuroscience, 2024)
Besides sepsis and malignancy, malperfusion is the third leading cause of tissue degradation and a major pathomechanism for various medical and surgical conditions. Despite significant developments such as bypass surgery, endovascular procedures, extracorporeal membrane oxygenation, and artificial blood substitutes, tissue malperfusion, especially of visceral organs, remains a pressing issue in patient care. The demand for further research on biomedical processes and possible interventions is high. Valid biological models are of utmost importance in enabling this kind of research. Due to the multifactorial aspects of tissue perfusion research, which include not only cell biology but also vascular microanatomy and rheology, an appropriate model requires a degree of biological complexity that only an animal model can provide, rendering rodents the obvious model of choice. Tissue malperfusion can be differentiated into three distinct conditions: (1) isolated arterial ischemia, (2) isolated venous congestion, and (3) combined malperfusion. This article presents a detailed step-by-step protocol for the controlled and reversible induction of these three types of visceral malperfusion via midline laparotomy and clamping of the abdominal aorta and caval vein in rats, underscoring the significance of precise surgical methodology to guarantee uniform and dependable results. Prime examples of possible applications of this model include the development and validation of innovative intraoperative imaging modalities, such as Hyperspectral Imaging (HSI), to objectively visualize and differentiate malperfusion of gastrointestinal, gynecological, and urological organs.
Gesehen am 24.02.2025